Perancangan Trainer Instalasi Penerangan Sebagai Media Pengembangan Instalasi Listrik - Antonov Bachtiar; Alfith Alfith (Jurnal Teknik Elektro, 2019)
A learning trainer for people to be able to understand how to do a good and proper electrical installation. The electrical installation system in a building must refer to the rules and regulations that apply in accordance with the PUIL 2011 and the 2014 electricity law. Components that are usually used for electrical installations are KWH meters, socket, MCB, switches, cables, fittings. Electrical installation is a system / circuit used to distribute electric power (Electric Power) to meet human needs in their lives. Electrical installations must meet the standards and laws that apply in Indonesia. The regulations relating to this problem are the General Requirements for Electrical Installation (PUIL), International Electrotecnical Commission (IEC).